Analysis of incidence and the value of SOFA and MOD scoring in predicting the outcome in acute mesenteric ischemia - Viswanathan, Rajasenthil; L., Santosh Vivekanandan; A., Ravi (International Surgery Journal, 2016)
Background: Acute mesenteric ischemia (AMI) is defined as a sudden loss of blood supply to visceral tissue, and it potentially results in intestinal infarction. AMI is an uncommon (1-2 per 1000 hospital admissions) but highly complex clinical problem. Mortality from AMI remains high despite an aggressive approach consisting of early diagnosis, restoration of arterial perfusion, resection of nonviable intestine, second-look laparotomy, and supportive intensive care with an average from published reports ranging from 30% to 65%. Moreover, most series have not shown any improvement in mortality over the last 2 decades, regardless of the therapeutic approach applied. While major advances in the technology and availability of imaging modalities have made earlier diagnosis and treatment more feasible, this has been counterbalanced by the contemporary AMI patient presenting at an advanced age and with more severe underlying comorbidities. Likewise, mesenteric ischemia remains a highly morbid condition. According to the literatures, early diagnosis, resection of the unviable bowel, recovery of adequate blood flow, second-look laparotomy, and supportive intensive management are the basis of appropriate management. Methods: The aim of the study was to analyse the incidence of AMI in our institution during April 2011– September 2013 and to study the demographics of that population and to compare the efficacy of SOFA vs MOD scoring in predicting the outcome of the patient with AMI. Treatment, consisting of surgical embolectomy or bypass grafting, has also yielded only modest improvements; some have championed an endovascular-first treatment paradigm. Moreover, accurate perioperative assessment of the risk of in-hospital mortality in patients with AMI is poorly defined. Results: In our study 60.7% of the patients presented to the casualty within 24hrs of symptoms. Patients who presented later than 24hrs (39.3%) had a higher mortality rate of 60.7%.When SOFA score increased to greater than 13 all patients succumbed to the disease with a mortality of 100% in the groups with SOFA score 13-16 and 17-20. When MOD score increased to greater than 12 all patients succumbed to the disease with a mortality of 100% in the groups with MOD score 13-16 and 17-20. On comparing the predictive outcome of SOFA vs MOD scoring system, both had similar results in predicting mortality (p value < 0.0001). Conclusions: To conclude, both SOFA and MOD scoring systems have similar values in predicting mortality for acute mesenteric ischemia. Other considerations such as age, comorbid illness DM /HTN/ /CAD /CVA do influence the outcome.